An evaluation of damage of bovine spermatozoa during processing, freezing and thawing. I leakage of glutamic-oxaloactetic transaminase (GOT) from spermatozoa - SOMADE, A.; KING , G. J.; MACHPERSON, J. W. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The activity of glutamic-oxaloacetic transaminase (GOT) in the seminal plasma of thirty ejaculates after collection; after extension, cooling and equilibration just before freezing; and other freezing and thawing were determined. After correction for the reduction in the activity of GOT caused by the extender and low temperatures the activity of enzyme was higher (P. 0.05) in post thaw semen than in either ejaculated or equilibrated semen just before freezing. However, the pre-freeze leakage of GOT from spermatozoa was similar to the leakage caused by freezing and thawing. The significance of these findings in relation to the use of GOT activity in seminal plasma as an index of spermatozoa damage were discussed.